Changes in Muscle Myostatin Expression in Obese Subjects after Weight Loss - Milan, G.; Dalla Nora, E.; Pilon, C.; Pagano, C.; Granzotto, M.; Manco, M.; Mingrone, G.; Vettor, R. (The journal of clinical endocrinology and metabolism, 2004)
Myostatin is a member of transforming growth factor-β superfamily that plays an important inhibitory role during muscle development; in fact mutations of myostatin gene result in a hypermuscular phenotype. Moreover myostatin-deficient mice have a significant reduction in fat depots and a depression of adipogenesis. Little is known about myostatin function in muscle growth regulation in humans and in particular during caloric restriction. In the present work we quantified by real-time RT-PCR myostatin expression in muscle biopsies of a group of morbidly obese patients before and after weight loss obtained by biliopancreatic diversion (BPD). The patients reduced body weight by 38.9%, mostly due to fat-mass loss, showing also a significant reduction in the 24-hour EE as assessed by the respiratory chamber. Myostatin mRNA levels result clearly decreased after weight loss, suggesting a role in counteracting the progressive decline of muscle mass after BPD. Myostatin may provide therefore another mechanistic explanation for the control of energy partitioning between protein and fat, working against muscle wasting. Our data suggest that myostatin might represent an important regulator of skeletal muscle size also in conditions of food restriction in obese subjects.